2019
DOI: 10.2967/jnumed.119.235879
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial-Temporal Ordering of Amyloid Pathology and Opportunities for PET Imaging

Abstract: Although clinical routine focuses on dichotomous and visual interpretation of amyloid PET, regional image assessment in research settings may yield additional opportunities. Understanding the regional-temporal evolution of amyloid pathology may enable earlier identification of subjects in the Alzheimer Disease pathologic continuum, as well as a finer-grained assessment of pathology beyond traditional dichotomous measures. This review summarizes current research in the detection of regional amyloid deposition p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
51
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 52 publications
9
51
0
Order By: Relevance
“…including the most recent and extensive staging work to date. 6 21 22 This consistent discrepancy between neuropathology and PET-only studies has been described previously, 23 and is likely to be influenced by signal distortion present in PET imaging. Due to the proximity of medial regions to white matter and the additional grey matter signal spill-in from the contralateral hemisphere, medial regions such as those in stage 1 and 2 in this work are more frequently classified as abnormal in PET imaging compared to lateral counterparts, even when levels of pathology are comparable.. 24 While the discrepancy with pathological studies might be due to sample size, resolution limitations and differences in technique such as the intrinsic signal distortion of PET imaging, remaining differences across PET studies could also be explained by methodological choices including the use of partial volume correction (PVC).…”
Section: A C C E P T E Dsupporting
confidence: 65%
“…including the most recent and extensive staging work to date. 6 21 22 This consistent discrepancy between neuropathology and PET-only studies has been described previously, 23 and is likely to be influenced by signal distortion present in PET imaging. Due to the proximity of medial regions to white matter and the additional grey matter signal spill-in from the contralateral hemisphere, medial regions such as those in stage 1 and 2 in this work are more frequently classified as abnormal in PET imaging compared to lateral counterparts, even when levels of pathology are comparable.. 24 While the discrepancy with pathological studies might be due to sample size, resolution limitations and differences in technique such as the intrinsic signal distortion of PET imaging, remaining differences across PET studies could also be explained by methodological choices including the use of partial volume correction (PVC).…”
Section: A C C E P T E Dsupporting
confidence: 65%
“…In addition, several studies have shown that measures of Aβ deposition below a threshold of established Aβ pathology carry critical information on initial pathological brain changes and may indicate appropriate time periods for interventions [19]. Moreover, the regional evolution of Aβ load may enable earlier identification of subjects in the AD pathologic continuum and may overcome dichotomous measures [20]. Regional information has shown to be relevant in staging Aβ pathology [21][22][23], tracking disease progression, and assessing the risk of cognitive decline [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Our results support this hypothesis especially when the amyloid deposition is plentiful, as in our study, and higher than 2 times amount in age-matched older persons, it should not be considered as the "normal" effect of aging. Conversely, the presence of high amyloid burden with global diffusion in the cerebral cortex is associated with an increased risk of developing AD over time [45,46].…”
Section: Discussionmentioning
confidence: 99%